A Transformation of the Mainland Chinese Market in Hong Kong's Tourism Industry. Issue 2 (3rd April 2022) - Bu, Naipeng (Tom); Fu, Xiaoxiao; Kong, Haiyan; Okumus, Fevzi
ABSTRACT: This paper analyzes the data of market size, profiles, and behavioral patterns of mainland Chinese tourists to Hong Kong from 1997 to 2018. With the economic boom and fewer restrictions on travel visas for mainland China, and attracted by a mixture of Eastern and Western cultures, the mainland Chinese market's access to Hong Kong has been strengthening for the past three decades, leading to a transformation of the mainland Chinese market in Hong Kong. This paper illustrates how mainland Chinese tourists have transformed from an international tourism market to a domestic one based on market access theory. Because the mainland Chinese market will continue to be Hong Kong's largest tourist source, more suitable travel policies should be launched for the sustainable development of tourism in Hong Kong.